Sustainable urbanization and green total factor productivity: evidence from China’s new-type urbanization plan - Yang, Zhijiu; Ji, Hongkun; Chen, Shuyan; Duan, Jiani; Liu, Lu (Technological and Economic Development of Economy, 2024)
Sustainable urbanization is significant in developing countries. This paper studies whether Chinese-type sustainable urbanization, that is new-type urbanization, promotes green total factor productivity (GTFP). We find that the new-type urbanization implementation in China, on average, significantly promotes GTFP by 3.2%. The positive effect of new-type urbanization on GTFP is correlated with promoting innovation, especially green innovation, and improving allocation efficiency. We do not find clear evidence for industrial upgrading, including industrial advancement and rationalization. This is because industrial upgrading is a gradual process and cannot be achieved shortly. Instead, we find that pilot cities might screen the entry of new firms and keep polluting firms out comparatively. The heterogeneous results indicate that the promotion effects on GTFP are more salient in regions with strong environmental regulation and adequate factor endowments. We have some practical implications for sustainable development in developing countries. First published online 17 September 2024